Intra-household bargaining in poor countries - Jean-Marie Baland; Roberta Ziparo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper is intended to bridge the theoretical literature describing efficient intra-household behaviour and the development literature that collects empirical regularities pointing toward the existence of strategic decision-making among spouses. It examines the key elements of the collective model and discusses its relevance to analysing intra-household behaviour in poor countries. It explores the role that risk and uncertainty, information asymmetries, power imbalances, arranged marriages, strategic investment, gender norms, and extended households play in the attainment of efficiency.
Keywords: D1; O1; D61; 330; household; efficiency; development; strategic behaviour